A taxonomy of strategic sourcing for defense forces in sub‐Saharan Africa. Issue 1 (2014) - ,; ,
<x xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to provide a taxonomy of strategic sourcing using the defense forces from a developing world context as a testing ground. This study builds upon the current resource‐based conceptualization of strategic sourcing as a construct to introduce the institutional orientation. Design/methodology/approach – This study adopts a descriptive and analytical research design of cross‐sectional nature to collect data from a sample of 120 respondents to examine the taxonomy of strategic sourcing for defense forces in sub‐Saharan Africa. Data were collected using an interviewee administered questionnaire and analysed using a confirmatory factor analysis (CFA). The conceptualization of strategic sourcing is presented using a CFA. Findings – Findings reveal that strategic sourcing is a multidimensional construct composed of: information sharing and risk management, strategic purchasing, institutions for sourcing, internal integration and performance assessment, supplier management and sourcing professionalism and ethics. Research limitations/implications – The study used cross‐sectional research design which limits monitoring behaviour over time. Cross‐sectional data do not allow control in the analysis for residual heterogeneity. Additionally, all item scales adapted in this study were developed in either manufacturing or profit‐oriented sector. Originality/value – A taxonomy for strategic sourcing within the defense forces is presented. This study is based on the observation that despite increased research, there remains a certain level of confusion surrounding the conceptualization of "strategic sourcing". Researchers attach a startling diversity of definitions and measures to the strategic sourcing concept. Its conceptualization and stability remains an important task for scholars to undertake. Besides, much research in strategic sourcing, are conceptual frameworks identifying key elements and procedures or processes to implement strategic sourcing with sparse empirical studies. The results of the study will be used for further research on strategic sourcing in the defense forces in sub‐Saharan Africa.